Neuroscience in the advertising of agri-food products: A beneficial tool or a public health hazard? - Izaguirre-Torres, Delia (2020)
Currently, methods based on neuroscience and technology (neurotechnology) are used to understand how people process different marketing stimuli. These methods could be used to generate adequate public health policies, but it is being used by agri-food companies to improve their marketing strategies and encourage the consumption of fast food, food intake high in sugar, salt, and saturated and trans fats, being the origin of non-communicable diseases such as obesity, heart attacks, cancer, hypertension and diabetes, as well as nutritional deficiencies, which constitute a great danger to people and public health. Neuroscientists have been using different technologies (functional magnetic resonance imaging (fMRI), electroencephalography (EEG), magnetoencephalography (MEG), positron emission tomography (PET), eye tracking, facial coding, galvanic skin response (GSR) or electrodermal activity (EDA), classical conditioning, Implicit-Association Test (TAI), and Neurofeedback or EEG Biofeedback), which provide new knowledge about marketing stimulus process ing and decision making. The evidence recommends that neuroimaging can reveal information about consumer preferences, which with other tools would be almost impossible to achieve. This review highlights the professional, ethical and scientific concerns applied to academic-industrial relations derived from the use of neuroscience or neuromarketing in advertising and in decision-making on the consumption of agri-food products, where neuroethics appears as a discipline of many importance. Future neuroscience research should be oriented to contribute to the effective satisfaction of needs, to differentiate and improve value offers, where the main interest is a situation of greater satisfaction and well-being for society.